The use of moral deliberation in empirical research in bioethics - Elma Zoboli (Revista Iberoamericana de Bioética, 2016)
The article presents an integrated empirical ethics research project that used the moral deliberation, according to the theoretical and philosophical conception, and methodical proposal of Diego Gracia, as a theoretical and methodological framework. The application showed the potential to realize the dynamics of the studied object in real life, making it possible, from the situation presented in the vignettes, for participants to include what they considered for dealing with the conflict of values. It also made the integration of philosophical and empirical approaches in bioethics research possible. The analytical category of prudence allowed the results to be assessed in a critical and comprehensive way.